Status of HIV infection among the pregnant women attending in outpatient department - Khanam, NN; Hussain, MA; Ferdous, J; Kulsum, SU; Alam, H; Chakma, B; Zabin, F (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):59-65 The abstract of this article is available on the PubMed website